Online grocery shopping in South Africa: underlying motivations and challenges - Maja, Kelelo Mpanana (My University, 2022)
While many countries imposed COVID-19-related restrictions, global online shopping adoption has recently improved, but not at the same rate as fashion and electronics. However, the disparity among the online segments is yet to be established. The study identified and examined factors influencing South African consumers’ intention to use online grocery shopping. A model was proposed to investigate and test hypotheses relating to effects of social influence (SI), word of mouth (WoM), brand intent, convenience, and order fulfilment constructs on customer purchase. Data was collected from 839 respondents via an online questionnaire. The Structural Equation Modelling (SEM) technique was used to evaluate the relationships between the constructs and customer purchase intention. Social influence, WoM, convenience, and order fulfilment significantly influenced customer purchase intentions, while brand intent showed an insignificant impact. Also, COVID-19 was found to significantly moderate the relationship between convenience and purchase intention, but Age and experience were insignificant.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, 2022
Keywords: Online grocery shopping; Online shopping influence; Online shopping motivations; Customer purchase intention; Online shopping; SDG-8: Decent work and economic growth